2007
DOI: 10.1093/hmg/ddm362
|View full text |Cite
|
Sign up to set email alerts
|

p21-activated kinase 1 promotes soluble mutant huntingtin self-interaction and enhances toxicity

Abstract: Huntington's disease (HD) is caused by a polyglutamine (polyQ) expansion in the huntingtin (htt) protein. While aggregation is a pathological hallmark of HD and related polyQ expansion diseases, the role of aggregates has been disputed. Here we report that p21-activated kinase 1 (Pak1) binds to htt in vivo and in vitro. Pak1 colocalized with mutant htt (muhtt) aggregates in cell models and in human HD brains. Pak1 overexpression enhanced the aggregation of muhtt. Furthermore, we observed SDS-soluble wild-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 31 publications
3
49
0
Order By: Relevance
“…4B). These data are consistent with those for the wild-type Htt-Pak1 or muHtt-Pak1 interactions (Luo et al, 2008).…”
Section: Mutant Htt Partially Protects Against Pak2 Cleavagesupporting
confidence: 89%
See 3 more Smart Citations
“…4B). These data are consistent with those for the wild-type Htt-Pak1 or muHtt-Pak1 interactions (Luo et al, 2008).…”
Section: Mutant Htt Partially Protects Against Pak2 Cleavagesupporting
confidence: 89%
“…However, much of the research on the normal functions of Htt has been restricted to neuronal systems, even though many of its normal functions might be generic. We previously reported that Pak1 binding to Htt promotes Htt-Htt interaction, and thus enhances muHtt oligomerisation and toxicity (Luo et al, 2008). Pak1, Pak2 and Pak3 have highly conserved protein sequences and similar functions (Bokoch, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, there are several other non-cancerous diseases which also require PAK1 (67,68,(73)(74)(75)(76)(77)(78)(79)(80)(81): Among them are AIDS (HIV-infection), malaria, Alzheimer's (AD), Huntington's (HD), infl ammatory diseases (asthma and arthritis), insulin-resistant diabetes (type 2), obesity, hypertension, seizures such as epilepsy, autistic diseases such as Fragile X syndrome, and learning defi cit (LD). Thus, propolis and other PAK1 blockers would serve as the effective (and safe) therapeutics for these diseases as well.…”
Section: Pak1-dependent Non-cancerous Diseasesmentioning
confidence: 99%